Designing labor market regulations in developing countries - Gordon Betcherman (IZA World of Labor, 2014)
Governments regulate employment to protect workers and to improve labor market efficiency. However, employment regulations can be controversial, often complicated by opposing ideological views. Thus, it is important for policymakers in developing countries to base decisions on empirical evidence of the impacts of these regulations. The majority of the evidence suggests that most countries have set their regulations in the appropriate range. But it can be costly when countries either overregulate or underregulate their labor market.
Keywords: J08; J38; J88; 330; labor market regulation; job security; minimum wages